Longitudinal atrophy characterization of cortical and subcortical gray matter in Huntington's disease patients. (18th December 2019) - Ramirez‐Garcia, Gabriel; Galvez, Víctor; Diaz, Rosalinda; Bayliss, Leo; Fernandez‐Ruiz, Juan; Campos‐Romo, Aurelio
Abstract: Huntington's disease (HD) is an inherited neurodegenerative disease with clinical manifestations that involve motor, cognitive and psychiatric deficits. Cross‐sectional magnetic resonance imaging (MRI) studies have described the main cortical and subcortical macrostructural atrophy of HD. However, longitudinal studies characterizing progressive atrophy are lacking. This study aimed to describe the cortical and subcortical gray matter atrophy using complementary volumetric and surface‐based MRI analyses in a cohort of seventeen early HD patients in a cross‐sectional and longitudinal analysis and to correlate the longitudinal volumetric atrophy with the functional decline using several clinical measures. A group of seventeen healthy individuals was included as controls. After obtaining structural MRIs, volumetric analyses were performed in 36 cortical and 7 subcortical regions of interest per hemisphere and surface‐based analyses were performed in the whole cortex, caudate, putamen and thalamus. Cross‐sectional cortical surface‐based and volumetric analyses showed significant decreases in frontoparietal and temporo‐occipital cortices, while subcortical volumetric analysis showed significant decreases in all subcortical structures except the hippocampus. The longitudinal surface‐based analysis showed widespread cortical thinning with volumetric decreases in the superior frontal lobe, while a subcortical volumetric decrease occurred in the caudate, putamen and thalamus with shape deformation on the anterior, medial and dorsal side. Functional capacity and motor status decline correlated with caudate progressive atrophy, while cognitive decline correlated with left superior frontal and right paracentral progressive atrophy. These results provide new insights into progressive volumetric and surface‐based morphometric atrophy of gray matter in HD. Abstract : This study shows widespread longitudinal cortical thinning in the whole cortical mantle of the brain. We also found specific shape deformations in caudate, putamen and thalamus. Furthermore, caudate progressive atrophy correlated with functional and motor performance decline, while superior frontal lobe atrophy correlated with cognitive decline. In short, progressive atrophy of superior frontal cortex and caudate may be a neuroimaging‐behavior predictor of disease progression.